Advanced microscopy technologies enable rapid response to SARS-CoV-2 pandemic - Cortese, Mirko; Laketa, Vibor (Cellular microbiology, 2021)
The ongoing SARS-CoV-2 pandemic with over 80 million infections and more than a million deaths worldwide represents the worst global health crisis of the 21th century. Beyond the health crisis, the disruptions caused by the COVID-19 pandemic have serious global socio-economic consequences. It has also placed a significant pressure on the scientific community to understand the virus and its pathophysiology and rapidly provide anti-viral treatments and procedures in order to help the society and stop the virus spread. Here, we outline how advanced microscopy technologies such as high-throughput microscopy and electron microscopy played a major role in rapid response against SARS-CoV-2. General applicability of developed microscopy technologies makes them uniquely positioned to act as the first line of defence against any emerging infection in the future.